1991
DOI: 10.1128/jcm.29.5.1054-1055.1991
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of cytomegalovirus antigenemia in allograft recipients

Abstract: A recently published technique for direct detection of cytomegalovirus (CMV) antigenemia was tested prospectively in 27 transplant recipients. Eighteen patients developed active CMV infections and 10 of the 18 experienced CMV syndrome. All of the infections were detected by classical virus isolation and/or serologic techniques. No antigenemia was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
2
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 10 publications
0
16
2
1
Order By: Relevance
“…Despite a number of studies in which the CMV antigenemia assay has been shown to be a highly sensitive method for diagnosing CMV infection, there are occasional reports of failures. In a prospective study, Miller et al [16] could not demonstrate CMV antigenemia in ten transplant patients with symptomatic CMV infection. Their presumption that processing delays might have been responsible for these negative results is supported by a recent report that a delay of 6 h in the transport of blood samples to the laboratory decreased the viral antigen detection rate by at least 80 % [8].…”
Section: Discussionmentioning
confidence: 89%
“…Despite a number of studies in which the CMV antigenemia assay has been shown to be a highly sensitive method for diagnosing CMV infection, there are occasional reports of failures. In a prospective study, Miller et al [16] could not demonstrate CMV antigenemia in ten transplant patients with symptomatic CMV infection. Their presumption that processing delays might have been responsible for these negative results is supported by a recent report that a delay of 6 h in the transport of blood samples to the laboratory decreased the viral antigen detection rate by at least 80 % [8].…”
Section: Discussionmentioning
confidence: 89%
“…Recently, the direct detection of CMV pp65 antigen in peripheral blood leukocytes was proposed as a useful marker of symptomatic CMV infection after renal transplantation [3]. However, two other groups failed to confirm these results [15,21], possibly due to some major technical drawbacks of the originally published peroxidase technique which, in our hands, led to…”
Section: Discussionmentioning
confidence: 81%
“…Miller et al [15] found no antigenemia at all in 18 actively infected transplant patients, 10 of whom showed CMV syndrome. The authors came to the conclusion that their failure to demonstrate CMV antigenemia was due to the investigation of 1-or 2-day-old specimens rather than freshly isolated blood samples.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Monitoring cytomegalovirus (CMV) antigenemia in patients who are immunocompromised because of organ transplantation or AIDS has been reported to be a useful marker of disease progression and treatment efficacy (2,3,7,9,10,(17)(18)(19)(20)(21). Although the antigenemia assay (AA) is very sensitive for detection of CMV, delays of as little as 6 h in transporting and processing specimens have been reported to reduce antigen detection rates as much as 80% (1).…”
mentioning
confidence: 99%